Destinasi Wisata Pintar untuk Meningkatkan Pengalaman Wisata Melalui Personalisasi Layanan (Studi Kasus Pada Perusahaan Pariwisata di Jawa Tengah) - Bambang Guritno; Haniek Listyorini; Renny Aprilliani; Y Sutomo (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2019)
Smart concepts into tourism destinations are dynamically embraced to connect stakeholders through technology platforms where information related to tourism activities can be exchanged directly. Instant information exchange has also created a huge data collection known as Big Data which may be computationally analyzed to reveal patterns and trends. Smart Tourism Destinations must make optimum use of Big Data by offering services that are suitable for the preferences of the user at the right time. In this connection, this paper aims to understand the contribution of how smart Tourism Destinations can potentially enhance the tourism experience through offering more personalized products or services to meet each visitor's unique needs and preferences. By using the skinative method and descriptive approach and the sample was taken through purposive sampling, the companies engaged in the tourism sector obtained the following research results: Understanding the needs, desires and desires of travelers became increasingly important for the competitiveness of tourism destinations. Therefore, the findings in this study are expected to be very beneficial for the number of tourism destinations.